PERSEPSI CIVITAS AKADEMIKA STAIN PADANGSIDIMPUAN TERHADAP RADIO KOMUNITAS PROXY FM STAIN PADANGSIDIMPUAN SEBAGAI MEDIA DAKWAH - Nasution, Fauziah (Institut Agama Islam Negeri Padangsidimpuan, 2014)
AbstractPerception someone has a significant impact on a person's attitude toward what he perceived, whereas the perception is not always true. Perception is a process that konpleks, which consists of a sensing, process, organization and interpretation. In the context of this study that examined is how the public perception of the existence Padangsidimpuan STAIN campus community radio FM Proxy STAIN Padangsidimpuan as media of dakwah. The background of this research presence in campus-based community radio in STAIN Padangsidimpuan. As a campus-based community broadcaster, the campus community participation in radio broadcasting sustainability has become a